2015
DOI: 10.1007/s12149-015-1040-0
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary report of breast cancer screening by positron emission mammography

Abstract: PEM screening appears to have potential for breast cancer screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Also, PET/MRI has already been shown useful in whole-body staging of patients with invasive ductal breast carcinoma and recurrent breast cancer (11,14,32). The potential for highly accurate characterization of breast lesions using PET techniques has been demonstrated by Yamamoto et al (16). In a screening setting with 265 women, those authors were able to show that abnormal 18 F-FDG uptake (detected with PEM) showed a sensitivity of 100% and a specificity of 84.5%.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, PET/MRI has already been shown useful in whole-body staging of patients with invasive ductal breast carcinoma and recurrent breast cancer (11,14,32). The potential for highly accurate characterization of breast lesions using PET techniques has been demonstrated by Yamamoto et al (16). In a screening setting with 265 women, those authors were able to show that abnormal 18 F-FDG uptake (detected with PEM) showed a sensitivity of 100% and a specificity of 84.5%.…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, like every imaging modality, MRI has its technically inherent limitations. Alternatively, PEM has already been proven to be helpful in characterizing small breast lesions (16). However, PEM scanners are specialized systems that cannot be used for a broader range of imaging, and they are not widely available yet.…”
mentioning
confidence: 99%
“…With an improved resolution of PEM, some research showed that the detection rate of PEM was 2.3%, which is better than that of PET/CT (Yamamoto et al 2015(Yamamoto et al , 2016. Other research suggested that the sensitivity of PEM is significantly better than that of PET in tumors that are 20 mm or smaller in size (Eo et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…SPECT radiation dose is about 1.1 mSv less than PEM. Furthermore, PEM is an expensive method as its cost is approximately 3.7 times higher than SPECT [40].…”
Section: Nuclear Medicine Imagingmentioning
confidence: 99%